Dinamika Kontrol Sosial Keluarga dan Teman Sebaya pada Remaja Berisiko Penyalahgunaan NAPZA - Hesti Kusumastuti; M. Noor Rochman Hadjam (Faculty of Psychology, Universitas Gadjah Mada, 2017)
The purpose of this research is to know in depth how the dynamics of social control family and peers on adolescents who are at risk of drug abuse. Method: This research method using a qualitative research method, which uses data collecting interviews and observation. Participant: This study focused on participants who are at risk of drug abuse with the following criteria: (a) willing to be a participant, (b) gender to male or female, (c) ± adolescents aged 15-18 years, (d) adolescents who are indicated are at risk of drug abuse. Result: The results of this study indicate that adolescents who are at risk of drug abuse are smoking and drinking. High-risk factors cause adolescents to be at risk for drug abuse, ie family conflicts, negative parental models, the involvement of negative activities with peers, and peer-to-peer conformity. This is supported by the weakness of protective factors in adolescent behavior at risk of drug abuse. Weak family controls supported by weak peer control will increase the risk rate for adolescent drug abuse behavior. This suggests that family and peer social controls are very influential to reduce the risk of adolescent drug abusers, especially in prevention and intervention.